Collections management practices at the Transvaal Museum, 1913-1964 : Anthropological, Archaeological and Historical - Ferreira, O.J.O. (Ockert Jacobus Olivier), 1940- (University of Pretoria, 2013)
Thesis (DPhil (Museology))--University of Pretoria, 2006.